2007
DOI: 10.1086/509892
|View full text |Cite
|
Sign up to set email alerts
|

Immaturity of Infection Control in Preterm and Term Newborns Is Associated with Impaired Toll‐Like Receptor Signaling

Abstract: The impaired infection control related to the functional immaturity of the neonatal immune system is an important cause of infection in preterm newborns. We previously reported that constitutive Toll-like receptor (TLR) 4 expression and cytokine secretion on lipopolysaccharide (LPS) stimulation increases with gestational age. Here, we analyzed constitutive monocyte TLR2 expression and evaluated the expression profiles of the proximal downstream adapter molecule myeloid differentiation factor 88 (MyD88). We fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
177
3
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(196 citation statements)
references
References 19 publications
12
177
3
4
Order By: Relevance
“…It is also in line with the low expression profile for TLR4 described in monocytes of ELBW infants as compared with term infants (22). In contrast, conflicting data come from recent observations made in a mouse model where NEC is induced by formula feeding, hypoxia, and LPS exposure.…”
Section: Articles Hbd2 Expression In Elbw Infants With Necsupporting
confidence: 71%
See 2 more Smart Citations
“…It is also in line with the low expression profile for TLR4 described in monocytes of ELBW infants as compared with term infants (22). In contrast, conflicting data come from recent observations made in a mouse model where NEC is induced by formula feeding, hypoxia, and LPS exposure.…”
Section: Articles Hbd2 Expression In Elbw Infants With Necsupporting
confidence: 71%
“…Mortality rate of severe NEC was 66% (n = 4) with no further deaths in the remaining patients. A total of 732 fecal samples were available (mean 11 per individual, range [5][6][7][8][9][10][11][12][13][14].…”
Section: Epidemiological Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cord blood is routinely used as a noninvasive, easily accessible neonatal sample as a surrogate for peripheral samples in immunological studies (24,26,27). However, the correlation between phagocytosis in cord and peripheral blood has not been reported previously.…”
Section: Phagocytosis In Newborn Whole Bloodmentioning
confidence: 99%
“…Toll-like receptors (TLRs) play a predominant role as a major family of PRR that act as essential "detectors" in the recognition of microbial pathogens by the innate immune system. We and others have shown that TLR-induced cytokine immune reactivity are profoundly attenuated in cord blood of very preterm neonates and develops asynchronously over the last trimester of gestation (6)(7)(8)(9)(10). These infants also display sustainably high levels of systemic inflammation, indicating a potential immune dysregulation that has also been associated with worsened clinical outcomes (11).…”
mentioning
confidence: 95%